A laboratory study of wave-induced local scour at an emergent pile breakwater. (15th February 2023) - Xu, Conghao; Huang, Zhenhua
Abstract: A pile breakwater is a row of closely-spaced piles, placed in a side-by-side arrangement, to dissipate wave energy and prevent coastal erosion. It is important to understand the local scour at a pile breakwater for its foundation design. This paper reports a set of wave-flume tests on the local scour around the piles in regular waves. A laser scanner was used to measure the change in the three-dimensional bed elevation. Five values of Keulegan–Carpenter number were examined in this study. Scour holes near the pile breakwater were developed due to the oscillatory jet flow through the gaps between adjacent piles, and sand ripples were observed on both sides of the structure. The migration of the sand ripples was either onshore or offshore, depending on the wave conditions. The maximum scour-hole depth had an exponential growth with the duration of wave attack, and the equilibrium depth was found to be deeper than that for a standalone pile. Both the scour-hole depth and length were found to be scaled by the pile diameter. The ripple length and steepness were in general agreement with recent empirical formulas in the literature in spite of the presence of a pile breakwater. Highlights: A set of experimental results of wave-induced scour at a pile breakwater are reported. Ripples and local scour hole are two major bed features. The scour-hole depth due to the oscillatory jet flow through a gap between piles is deeper than that corresponding to a standalone pile. The ratio of bottom excursion amplitude to sand diameter controls ripple length and steepness.